Paying for online news: What? How Much? And Why (Not)? Predictors of paying intent for a non-mainstream but popular news organization - Spyridou, Lia Paschalia; Manavopoulos, Vasilis (My University, 2021)
Funding digital journalism requires news organisations to reduce their reliance on advertising revenue, gain a clearer understanding of the economic value of news and develop better insight into consumers and their willingness to pay for news (Pickard, 2016). Although a recurrent issue in journalism studies, declining levels of trust in journalism and mounting evidence pointing to diminished professional autonomy (Peters & Broesma, 2012; Papadopoulou & Maniou, 2021) confirm a long-standing idea that the financial crisis of the press is closely related to a crisis of civic adequacy (Franklin, 2014). Not surprisingly, slow journalism endeavors trying to offer more civically useful and explanatory news diets (Le Masurier, 2015) and ‘hybrid outlets’ that do journalism which combines mainstream and alternative traits are on the rise. Whilst journalism is faced with the need – or almost the urgency – to rethink, reinvent and redefine messages, routines, and processes (Romero-Rodríguez et al, 2021), it is the first time in journalism’s history that identification of viable business models is so compelling and so hard to define. The collapse of the traditional advertising model on one hand, and the web’s free news culture on the other (Bakker, 2012) make it increasingly difficult for news organizations to cope with professional and commercial standards. The current hope is that “readers will come to the rescue” (Benson, 2019) through subscriptions, paywalls and micropayments. However, attention is a scarce and fluid commodity (Myllylahti, 2019), whilst the subscription model seems to work for well-established legacy media or for premium content (Benson, 2019). A relatively small amount of studies (Goyanes, 2014) have examined the relationship between individual-level attributes and the willingness to pay for online news with generally contradictory findings (Himma-Kadakas, 2015) that vary significantly between different national contexts (see Fletcher & Nielsen, 2017). This study provides evidence from a cooperative, Left-leaning Greek newspaper (EfSyn) that accounts for approximately 12% of the daily press market share and employs a voluntary contribution model for its online counterpart (similar to the e.g. the Guardian in the UK and die Tageszeitung in Germany). Data was collected through an online questionnaire posted on the paper’s website in January 2017. Approximately 3.5 thousand responses were collected to a questionnaire of about 50 items. Logistic regression was used to examine individual-level characteristics and attitudes that are associated with having made a monetary contribution to the newspaper and intention to do so in the future. In line with previous research, the majority of respondents have never contributed to the newspaper although a significantly larger segment of the sample claimed they would be willing to do so (39%). In terms of individual predictors, age, ideological self-placement and participatory behavior through Efsyn were found to be significant predictors of past contribution. Also, EfSyn’s attributes (plurality of topics, a critical stance and unique analysis) were found to be significant predictors of payment. Combining the results from past paying behavior and future paying intention, it may be argued that news consumers fall into three categories: (a) those who will never pay; for them online news is a free service, (b) those who might pay, but this decision is seen in the context of buying a product; for them the medium’s attributes are probably more important than ideology, and (c) those who might pay but who view such a voluntary contribution as a political/ideological act; for them specific product characteristics aren’t as important as the characteristics of the organization they are supporting.This study adds to the growing literature on the antecedents involved in paying behaviour for non-mainstream but popular news organizations.
Keywords: Journalism; Crowdfunding